(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-3-20-32 Lushka Nagulnova is a wife of Makar Nagulnov and lover of political antagonists Timofey Rvaniy and Semen Davydov. She plays one of the key roles in the plot and in the system of characters of M.A. Sholokhov’s novel “Virgin Soil Upturned”. The inner form (A. A. Potebnya) of her character is vast and it’s based on usual artistic methods: portrait, verbal self-portrait, different character names (from Lushka to Lukerya Nikitichna and Glikeryia), artistic detail, numerous associative plans of description, landscape and its odorative component, literary allusions and others. The image of Lushka Nagulnova is embodied by Sholokhov as complex and multifaceted one, with a certain evolution. Other ∗ © Васильев С. А., 2025 characters succinctly characterize her as a snake (Nagulnov), that is, a temptress, and a swindler (Shaloy) – a rogue, an impudent person. Lushka takes the death of Timofey Rvany hard, not embarrassed to express her feelings in public. Nevertheless, there is a reason to believe that when she says goodbye to Makar, she begins to understand how much he loved her, that a moral turn has begun in her, which is hinted at by the later information about her work as a hauler in the mine. However, the evolution of the image ends with Lushka, having married a wealthy and influential engineer Sviridov, becoming a new Soviet bourgeois, completely occupied with the material aspects of life and losing the charm that was so characteristic of her earlier, the “charm of a person”. Key words: M.A. Sholokhov, “Virgin Soil Upturned”, image of the character, inner form, name, portrait